Zero at the Bone - Whish-Wilson, David (Penguin Australia, 2013)
For ex-detective Frank Swann, being on the outside of Western Australia's police force is the only way to get justice done.Perth in 1979 is a city of celebration and corruption. There are street parties, official glad-handing – even a royal visit – to commemmorate a century and a half since colonisation. But behind the festivities a new kind of land grab is going on, this time for mining leases. The price of gold is up, and few are incorruptible before its lure. When Swann is hired to probe the suicide of a well-regarded geologist, he's drawn into a mire of vice and fraud that has at its heart a lust for wealth that verges on a disease . . .